Genomic Characterization of hlyF-positive Shiga Toxin–Producing Escherichia coli, Italy and the Netherlands, 2000–2019 - Gigliucci, Federica (Emerg Infect Dis, 2021)
Shiga toxin–producing Escherichia coli (STEC) O80:H2 has emerged in Europe as a cause of hemolytic uremic syndrome associated with bacteremia. STEC O80:H2 harbors the mosaic plasmid pR444_A, which combines several virulence genes, including hlyF and antimicrobial resistance genes. pR444_A is found in some extraintestinal pathogenic E. coli (ExPEC) strains. We identified and characterized 53 STEC strains with ExPEC-associated virulence genes isolated in Italy and the Netherlands during 2000–2019. The isolates belong to 2 major populations: 1 belongs to sequence type 301 and harbors diverse stx(2) subtypes, the intimin variant eae-ξ, and pO157-like and pR444_A plasmids; 1 consists of strains belonging to various sequence types, some of which lack the pO157 plasmid, the locus of enterocyte effacement, and the antimicrobial resistance–encoding region. Our results showed that STEC strains harboring ExPEC-associated virulence genes can include multiple serotypes and that the pR444_A plasmid can be acquired and mobilized by STEC strains.